From waste to value: key insights and lessons learned from biogas initiatives in the Global South - Somorin, Tosin; Bodach, Susanne; Tripathi, Mansi (International Water Management Institute, 2025)
Biogas technology offers a promising pathway for circular bioeconomy transitions in the Global South by turning organic waste into clean energy and nutrient-rich byproducts. Through anaerobic digestion, this approach supports climate mitigation, reduces environmental pollution, and enhances energy access and rural livelihoods. However, large-scale implementation remains limited due to complex barriers spanning political, financial, social, and technical dimensions. Drawing on case studies from Asia and Africa, this report identifies key drivers of successful biogas programs—including strong policy support, financing mechanisms, market development, and community engagement—while underscoring challenges such as fragmented governance, high upfront costs, and low public acceptance. Overcoming these requires integrated strategies that promote enabling environments, capacity building, standardization, and investment readiness. Scaling biogas technologies in low- and middle-income countries can catalyze sustainable development by aligning climate action with inclusive waste management and renewable energy.